(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Information literacy plays a crucial role in empowering students to effectively address the challenges they encounter and attain their goals in both their personal and academic pursuits. Therefore, university students comprehend the significance of research work and their proficiency in executing the needed research duties, which influences the correctness of the research outcomes. The reliability and moral principles of individuals reflect the effectiveness of their psychological empowerment. Hence, the objective is to uncover the correlation between information enlightenment and psychological empowerment, taking into account certain demographic characteristics among graduate students at the institution. The researcher employed a descriptive methodology and developed two measures, one for measuring information enlightenment and the other for assessing psychological empowerment. These scales were then administered A total of 85 male and female students, who are currently pursuing master’s and doctoral degrees at the College of Education, King Khalid University, were included in the sample. The results revealed a robust and significant correlation between knowledge enlightenment and psychological empowerment among postgraduate students at King Khalid University. Significant disparities in information literacy scores can be seen based on age, gender, and level of education, particularly among older individuals, men, and those with PhD degrees. Doctoral students have a higher level of competence in psychological empowerment compared to master’s students. The study suggested the necessity of educating university students on the significance of information enlightenment and improving their psychological empowerment.